2015
DOI: 10.1039/c4sm02724h
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of the lamellar to bicontinuous gyroid cubic (QGII) phase transitions under limited hydration conditions

Abstract: Non-equilibrium pathways of lyotropic phase transitions such as the lamellar to inverse bicontinuous cubic phase transition are important dynamical processes resembling cellular fusion and fission processes which can be exploited in biotechnological processes such as drug delivery. However, utilising and optimising these structural transformations for applications require a detailed understanding of the energetic pathways which drive the phase transition. We have used the high pressure X-ray diffraction techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…2, a-c resembling the inverse of the lamellar-to-cubic phase transition described by Tang and co-workers (Fig. 5 in (40)). This conformational change appears to be driven by the hydrophobic interactions in the system, as the structural rearrangements (from Fig.…”
Section: Human Skin Glycosylceramides Stabilize a Folded Bilayer Structure With Cubic-like Symmetrysupporting
confidence: 59%
“…2, a-c resembling the inverse of the lamellar-to-cubic phase transition described by Tang and co-workers (Fig. 5 in (40)). This conformational change appears to be driven by the hydrophobic interactions in the system, as the structural rearrangements (from Fig.…”
Section: Human Skin Glycosylceramides Stabilize a Folded Bilayer Structure With Cubic-like Symmetrysupporting
confidence: 59%
“…This process should also take place while D and G twins are formed. It has been suggested that bicontinuous phases can be transformed from lamellar phases by forming so-called interlamellar attachments (ILAs) between adjacent bilayers (Squires et al, 2002;Conn et al, 2006;Tang et al, 2015). More recently, direct imaging has also shown that ILAs emerge as open necks between parallel planes (Demurtas et al, 2015).…”
Section: Bcs Twinning As Stacking Faultmentioning
confidence: 99%
“…This would be consistent with the hypothesis that the cell changes its lipid composition to lower the energetic barrier to entering the next phase of the cell cycle [ 16 ]. Furthermore, work on replicating lipid systems with similar dimensions to those observed in nature show that they are sensitive to parameters such as composition and surface charge [ 37 , 52 , 56 ]. Control of these parameters, with respect to cell size, therefore forms an important part of managing the structure of the cell through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%